An uncertainty model for the curing process of transversely fiber reinforced plastics. Issue 1 (25th January 2021) - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf
Abstract: Lightweight structures, such as fiber reinforced plastics (FRPs), become increasingly important due to their excellent mechanical and lightweight properties. During the manufacturing process, curing of the matrix is a dominant effect as it is highly temperature dependent and influences strongly the mechanical, thermal and chemical properties of FRPs. Variations in the manufacturing process, measurement errors and missing or incomplete information are typical causes of uncertainties. This contribution presents a framework for an uncertainty model for the curing process of transversely fiber reinforced plastics. As a key idea the overall effective properties of the cured matrix during the manufacturing process are calculated by uncertainty homogenization models.